Do NOACs Improve Antithrombotic Therapy in Secondary Stroke Prevention in Nonvalvular Atrial Fibrillation?. Issue 38 (September 2015) - Lin, Yi-Pin; Tan, Teng-Yeow; Bix., Gregory
<x xml:space="preserve">Abstract</x> Abstract Guidelines recommended oral anticoagulant (OAC) for ischemic stroke patients related to atrial fibrillation (AF). But, underprescription or underdose of warfarin was observed worldwide. We aimed to explore if the use of antithrombotic therapy in nonvalvular AF (NVAF) ischemic stroke patients improved after novel oral anticoagulants (NOACs) became available. Between January 2011 to December 2013, 360 acute ischemic stroke patients related to NVAF were recruited. Patients were categorized into 2 groups based on the date (July 2012) of NOACs' availability. There were 184 patients recruited before July 2012, and whereas 176 patients after July 2012. Demographic data, interested factors, and the percentage of patient on OAC were compared. One month after discharge, percentage of OAC utilization was significantly higher (29% versus 41%; P = 0.022) as well as effective anticoagulation (22.2% versus 80.6%; P < 0.001); warfarin utilization was significantly less (28.3% versus 11%; P < 0.001) after NOACs became available. Antiplatelet agent utilization was high in 2 groups (57% versus 52%; P = 0.36). Age (odd ratios [OR] 0.947; 95% confidence intervals [CI] 0.912–0.984; P = 0.005), Barthel index (OR 1.012; 95% CI 1.000–1.025; P = 0.05), and NOACs' availability (OR 1.857; 95% CI 1.086–3.175; P = 0.024) were the significant factors affecting the use of OAC. A higher percentage of NVAF ischemic stroke patients returning for their 1-month follow-up were treated with NOACs than with warfarin. The use of antithrombotic therapy improved after NOACs became available. But, the majority of the patients were still received antiplatelet agent for emboli stroke prevention.